Oxygen diffusion in the fluorite-type oxides CeO2, ThO2, UO2, PuO2, and (U, Pu)O2 - Kato, Masato; Watanabe, Masashi; Hirooka, Shun; Vauchy, Romain (Frontiers in Nuclear Engineering, 2023)
This study evaluates the self-diffusion and chemical diffusion coefficients of oxygen in the fluorite-type oxides CeO2, ThO2, UO2, PuO2, and (U, Pu)O2 using point defect chemistry (oxygen vacancies and interstitials). The self-diffusion coefficient changed in proportion to the 1/n power of oxygen partial pressure, similar to the defect concentration. All parameters used to represent the diffusion coefficients were determined, and the experimental data were accurately stated. The defect formation and migration energies of the oxides were compared, and the change in Frenkel defect concentration was found to affect the high-temperature heat capacities of CeO2 and ThO2. The oxygen chemical diffusion was evaluated in the oxides, excluding the line compound ThO2, and the coefficients increased dramatically around the stoichiometric composition, i.e., the chemical diffusion coefficient was much higher at stoichiometric composition, with the oxygen-to-metal ratio equal to 2.00, than in low oxygen-to-metal oxides. This difference altered the mechanism of the reduction and oxidation processes. In the reduction process, the chemical diffusion control rate was dominant and a new phase with the oxygen-to-metal ratio equal to 2.00 was formed, which then expanded from the surface in the oxidation process from a low oxygen-to-metal ratio to the stoichiometric composition.